Research on the Behavior of the Steel Plated Shear Wall by Finite Element Method. (30th May 2013) - Mortazavi, S. M. R.; Ghassemieh, M.; Ghobadi, M. S.
Abstract : From the early' 70s till today, steel shear walls have been used as the primary lateral force resisting system in some of the significant buildings around the world. To assist understanding the behavior of this system, there have been research programs in USA, Canada, Japan, and UK. This research presents the dynamic and cyclic behavior of steel plated shear wall. In order to simulate the behavior of such a wall structure, finite element method of analysis is implemented. Several analytical models are implemented, in order to obtain the dynamic as well as cyclic behavior of such system. The material nonlinearity as well as geometrical nonlinearity along with the postbuckling behavior of steel plate subjected to cyclic loading has also been employed. The hysteresis diagrams of steel shear wall system in terms of storey shear drift are presented. The results obtained from the analyses are compared to some experimental results reported by other researchers previously. The nonlinear time history analysis of such system is carried out for different seismic response spectra. Finally, the significant factors and parameters of the steel plated shear wall which affect the overall behavior of such system are acknowledged and their effects were recognized.